2016
DOI: 10.1159/000450748
|View full text |Cite
|
Sign up to set email alerts
|

A Difference in the Incidences of Hypersensitivity Reactions to Original and Generic Taxanes

Abstract: Purpose: To compare incidences of hypersensitivity reaction (HSR) between original and generic taxanes including paclitaxel and docetaxel. Methods: We conducted a prospective study enrolling all patients receiving taxanes at King Chulalongkorn Memorial Hospital. Taxanes were infused accordingly to the step-wise rate escalation protocol at this hospital. Active surveillance for HSRs was performed. During the study period, there was only 1 generic brand used for each taxane. We primarily compared the incidences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 18 publications
1
2
0
5
Order By: Relevance
“…Furthermore, hypersensitivity reactions are important adverse events in paclitaxel-based treatment, and can lead to death. Studies have shown that 8–14% of patients develop hypersensitivity reactions during paclitaxel-based chemotherapy [37, 38]. In our study, a hypersensitivity reaction was not observed, a result that is consistent with that in other studies [39–41].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, hypersensitivity reactions are important adverse events in paclitaxel-based treatment, and can lead to death. Studies have shown that 8–14% of patients develop hypersensitivity reactions during paclitaxel-based chemotherapy [37, 38]. In our study, a hypersensitivity reaction was not observed, a result that is consistent with that in other studies [39–41].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, activated basophils, one of the types of leukocytes, produce large amounts of T helper type 2 (Th2) cytokines, 33) and basophil CD203c is expected as a promising biomarker for the prediction of severe carboplatinrelated anaphylaxis. 34) Further investigation is necessary to elucidate the mechanism of docetaxel-related anaphylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…La prevalencia de las reacciones varía entre estudios. Se ha reportado una prevalencia del 2% al 10% para taxanos [46,47]. Para platinos oscila entre el 46% en pacientes que han recibido más de 15 infusiones, hasta el 27% en aquellos que recibieron 7 o más, y 1% en individuos que han recibido 6 o menos infusiones [48].…”
Section: Epidemiologíaunclassified